Polypeptide N-acetylgalactosamine transferase 3: a post-translational writer on human health - Garay, Yohana Camila (2022)
Polypeptide N-acetylgalactosamine transferase 3 (ppGalNAc-T3) is an enzyme involved in the initiation of O-GalNAc glycan biosynthesis. Acting as a writer of frequent post-translational modification (PTM) on human proteins, ppGalNAc-T3 has key functions in the homeostasis of human cells and tissues. We review the relevant roles of this molecule in the biosynthesis of O-GalNAc glycans, as well as in biological functions related to human physiological and pathological conditions. With main emphasis in ppGalNAc-T3, we draw attention to the different ways involved in the modulation of ppGalNAc-Ts enzymatic activity. In addition, we take notice on recent reports of ppGalNAc-T3 having different subcellular localizations, highlight critical intrinsic and extrinsic functions in cellular physiology that are exerted by ppGalNAc-T3-synthesized PTMs, and provide an update on several human pathologies associated with dysfunctional ppGalNAc-T3. Finally, we propose biotechnological tools as new therapeutic options for the treatment of pathologies related to altered ppGalNAc-T3. KEY MESSAGES: ppGalNAc-T3 is a key enzyme in the human O-GalNAc glycans biosynthesis. enzyme activity is regulated by PTMs, lectin domain and protein-protein interactions. ppGalNAc-T3 is located in human Golgi apparatus and cell nucleus. ppGalNAc-T3 has a central role in cell physiology as well as in several pathologies. Biotechnological tools for pathological management are proposed.